Advertising art in the Art Deco style - Menten, Theodore (Dover books on graphic arts, printing, calligraphy, advertising and related areas, 1975)
363 ads, posters, trademarks and other commercial graphics -- 22 in full color -- that pictorially chronicle the rise of Art Deco in Europe and America. Artists include Kinger, Teague, Carlu, Lepape, Darcy, Brill.